2016
DOI: 10.1016/j.joto.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cues and the effect of their enhancement on speech perception in older adults – A scoping review

Abstract: Temporal envelope is a low frequency amplitude modulation conveying segmental and suprasegmental information during speech perception. Unfortunately, we seldom find ourselves in completely quiet listening environments and noise, commonly found in the surrounding environment, obscures both the fine structure cues and partly the temporal envelope cues in speech. Available temporal content of speech emanating from noise is often enough to convey required information in normal hearing individuals. However, the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Noise tends to obscure amplitude modulations in speech that are essential for its comprehension (Bidelman, 2016; Shannon et al, 1995; Swaminathan and Heinz, 2012). In contrast, in cases of speech-on-speech masking, listeners can better utilize spectral dips for perception, resulting in less effective masking than continuous noise (Peters et al, 1998; Shetty, 2016). FFR changes related to speech-on-speech masking and SNR were evident in both the time and frequency domain results, consistent with previous studies (Bidelman and Krishnan, 2010; Bidelman, 2016; Hornickel et al, 2011; Song et al, 2011; Tierney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Noise tends to obscure amplitude modulations in speech that are essential for its comprehension (Bidelman, 2016; Shannon et al, 1995; Swaminathan and Heinz, 2012). In contrast, in cases of speech-on-speech masking, listeners can better utilize spectral dips for perception, resulting in less effective masking than continuous noise (Peters et al, 1998; Shetty, 2016). FFR changes related to speech-on-speech masking and SNR were evident in both the time and frequency domain results, consistent with previous studies (Bidelman and Krishnan, 2010; Bidelman, 2016; Hornickel et al, 2011; Song et al, 2011; Tierney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the distortion of speech after processing could also be a reason for the individual differences and small benefits in SI scores. Although our algorithms were optimised purely on the basis of the simulated outcomes of a biophysical model [50], additional signal-processing techniques could be applied after the optimisation procedure to minimise the negative effects that envelope processing might introduce (e.g., [37,39,44,47,93,94]). The presented algorithms rely on instantaneous processing of the temporal envelope (RMS window of <1 ms), which has been argued to lead to non-linear distortion and poor sound quality in dynamic-range compression [17,32,34,35,37,[94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic modifications of the speech-envelope shape and periodicity can improve SI [18,[32][33][34][35][36][37], especially in connection with hearing through cochlear implants [38][39][40][41][42][43]. Several studies have shown that envelope enhancement can be beneficial for speech recognition in individuals with temporal processing deficits [22,36,[44][45][46][47][48]. Here, we go beyond these conventional approaches to develop a model-based type of auditory envelope processing that operates directly on the signal waveform to counteract the functional consequences associated with CS.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the amplitude modulation depth, and alters the envelope shape, and thus alters the intelligibility-relevant temporal cues contained in speech (Stone & Moore, 1992). The envelope of speech is thus not just a simple acoustic feature of speech but also associated with speech comprehension (Poeppel & Assaneo, 2020; Shetty, 2016).…”
Section: Introductionmentioning
confidence: 99%